The Literariness of Media Art - Benthien, Claudia (Taylor & Francis, 2019)
"Language can be this incredibly forceful material-there's something about it where if you can strip away its history, get to the materiality of it, it can rip into you like claws" (Hill in Vischer 1995, 11). This arresting image by media artist Gary Hill evokes the nearly physical force of language to hold recipients in its grip. That power seems to lie in the material of language itself, which, with a certain rawness, may captivate or touch, pounce on, or even harm its addressee. Hill's choice of words is revealing: 'rip into' suggests not only a metaphorical emotional pull but also the literal physicality of linguistic attack. It is no coincidence that the statement comes from a media artist, since media artworks often use language to produce a strong sensorial stimulus. Media artworks not only manipulate language as a material in itself, but they also manipulate the viewer's perceptual channels. The guises and effects of language as artistic material are the topic of this book, The Literariness of Media Art.